Kemampuan komunikasi matematis dan self-confidence siswa pada materi sistem persamaan linear tiga variabel di desa sukaresmi - Hapsoh Hapsoh; Deddy Sofyan (Institut Pendidikan Indonesia, 2022)
In reality, mathematical communication skills and lack of trust in students in Indonesia are still relatively low. Indications of low mathematical communication skills are seen from the results of a survey conducted by the OECD that shows that students' ability in mathematics learning is at a low level. Indications of weak self-confidence in learners are when students lack confidence when asked to express their opinions on the concept of normality discussed. The purpose of the researcher is to know the mathematical communication skills and self-confidence of students in the material of the three-variable linear equation system. This study was conducted on high school students in the Sukaresmi area with 6 students sampled. The findings in this study include the mathematical communication skills of each student in the SPLTV materials vary, including students with low, medium, and high mathematical communication skills. Furthermore, the achievement of self-confidence in students can also be seen from the level of interpretation obtained by students, namely moderate and high. Students with high self-confidence interpretation tend not to understand the advantages or disadvantages that they have, while students with self-confidence interpretation are not confident in their own abilities, are anxious about solving problems, feel depressed, and tend to be irresponsible. Pada kenyataannya kemampuan komunikasi matematis dan kurangnya rasa percaya pada peserta didik di Indonesia masih tergolong rendah. Indikasi rendahnya kemampuan komunikasi matematis dilihat dari hasil survei yang dilakukan oleh OECD yang menunjukan bahwa kemampuan siswa dalam pembelajaran matematika berada pada level yang rendah. Indikasi lemahnya self-confidence peserta didik adalah saat peserta didik kurang percaya diri ketika diminta untuk mengemukakan pendapatnya mengenai konsep kematematikaan yang dibahas. Adapun tujuan dari penelitian tersebut yaitu untuk mengetahui kemampuan komunikasi matematis dan self-confidence siswa pada materi sistem persamaan linear tiga variabel. Penelitian ini dilakukan pada siswa tingkat SMA/Sederjat di daerah Sukaresmi dengan 6 orang siswa yang dijadikan sampel. Hasil temuan dalam penelitian ini diantaranya kemampuan komunikasi matematis setiap siswa pada materi SPLTV berbeda-beda, diantaranya siswa dengan kemampuan komunikasi matematis rendah, sedang, dan tinggi. Selanjutnya pencapaian self-confidence pada siswa juga dapat dilihat dari tingkat interpretasi yang diperoleh oleh siswa yaitu sedang dan tinggi. Siswa dengan interpretasi self-confidence yang tinggi cenderung tidak memahami kelebihan maupun kekurangan yang dimilikinya, sedangkan siswa dengan interpretasi self-confidence yang sedang kurang percaya pada kemampuan dirinya sendiri, cemas dalam menyelesaikan permasalahan, merasa tertekan serta cenderung tidak bertanggung jawab.